2018
DOI: 10.1016/j.jbtep.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental modification of dysfunctional interpretations in individuals with contamination concerns

Abstract: Completion of the CBM-I was beneficial for reducing dysfunctional interpretations relevant to naturally-occurring contamination concerns and, importantly, this reduction may help those individuals approach feared situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 81 publications
2
5
0
Order By: Relevance
“…As predicted, our positive training led to a greater increase in adaptive interpretive bias towards ambiguous contamination-related situations whereas the neutral training did not. This finding converges with those reported by Beadel et al (2016) and Conley and Wu (2018), who were also able to train an adaptive bias in individuals with contamination concerns, despite using either a different set of training items or CBM-I methodology. Importantly, like Conley and Wu (2018), we showed that our positive training, relative to neutral training, was associated with less avoidance of contaminants on our behavioural approach tasks.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As predicted, our positive training led to a greater increase in adaptive interpretive bias towards ambiguous contamination-related situations whereas the neutral training did not. This finding converges with those reported by Beadel et al (2016) and Conley and Wu (2018), who were also able to train an adaptive bias in individuals with contamination concerns, despite using either a different set of training items or CBM-I methodology. Importantly, like Conley and Wu (2018), we showed that our positive training, relative to neutral training, was associated with less avoidance of contaminants on our behavioural approach tasks.…”
Section: Discussionsupporting
confidence: 90%
“…These studies matched the CBM-I training material to the target population and showed that this significantly reduced contamination-related interpretive bias, relative to control training (Beadel et al, 2016;Conley & Wu, 2018) and when the training material was not related to contamination concerns (i.e., acrophobia; Beadel et al, 2016). However, only Conley and Wu (2018) showed that CBM-I was associated with less behavioural avoidance of contaminants on their behavioural approach task. Study-specific limitations notwithstanding, both studies support the idea that CBM-I is more likely to be effective in shifting interpretive biases, symptoms and/or behaviour if the training target and population align.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several psychological models have been introduced to examine the etiology, maintenance, and severity of OCD, and currently, the CBT model has the most experimental support (Conley & Wu, 2018). According to this model, the manner of interpreting and paying attention to unwanted and troublesome thoughts and impulses causes distress and leads to repetitive and ritualistic behaviors (Clayton, Richards, & Edwards, 1999;Clerkin & Teachman, 2011).…”
mentioning
confidence: 99%